Expression of the Two Nested Overlapping Reading Frames of Turnip Yellow Mosaic Virus RNA Is Enhanced by a 5′ Cap and by 5′ and 3′ Viral Sequences - Matsuda, Daiki (American Society for Microbiology, 2004)
The translation efficiency of an mRNA molecule is typically determined by its 5′- and/or 3′-untranslated regions (UTRs). Previously, we have found that the 3′-UTR of Turnip yellow mosaic virus (TYMV) RNA enhances translation synergistically with a 5′ cap. Here, we use a luciferase reporter system in cowpea protoplasts to show that the 5′ 217 nucleotides from TYMV genomic RNA enhance expression relative to a vector-derived 17-nucleotide 5′-UTR. Maximum expression was observed from RNAs with a cap and both 5′ and 3′ TYMV sequences. In paired reporter constructs, the 5′ 217 nucleotides harboring the UTR and the first 43 or 41 codons of the two overlapping TYMV open reading frames (ORFs), ORF-69 and ORF-206, respectively, were fused in frame with the luciferase gene. This allowed expression from the initiation codon of each ORF (AUG(69) and AUG(206)) to be monitored separately but from the normal sequence environment. Expression from both AUG codons was heavily dependent on a 5′ cap, with a threefold-higher expression occurring from AUG(69) than from AUG(206) in the presence of the genomic 3′-UTR. Changes that interrupted the cap/3′-UTR synergy (i.e., removal of the cap or TYMV 3′-UTR) resulted in a higher proportion of initiation from AUG(206). Mutation of the 3′-UTR to prevent aminoacylation, as well as deletion of 75% of the 5′-UTR, likewise resulted in a lower ratio of expression from AUG(69) relative to AUG(206). Mutation of each AUG initiation codon increased initiation from the other. Taken together, these results do not fully conform to the expectations of standard leaky ribosomal scanning and leave open the precise mechanism of ribosome commitment to AUG(69) and AUG(206). However, our observations do not support a recent proposal based on in vitro studies in which the 3′-UTR is proposed to direct cap-independent initiation specifically at AUG(206) and not at AUG(69) (S. Barends et al., Cell 112:123-129, 2003).